The type III secretion system translocases IpaC, SipC, and BipC are partially folded alpha helical proteins lacking in tertiary structures - Jacob M. Kroh; Amritangshu Chakravarty; Supratim Dey; Roberto N. De Guzman (PLoS ONE, 2025)
The Type III secretion system (T3SS) is essential in the virulence of many bacterial pathogens that cause infectious diseases in humans. The T3SS consists of an injectisome that bacteria use to inject virulence proteins directly into human cells to initiate infection. Part of the injectisome is the translocon, which forms a pore on the host membrane to allow the passage of virulence proteins into the host. The translocon is assembled from two membrane proteins, termed major and minor translocases, based on their relative sizes from each other. Both major and minor translocases are essential for virulence. The atomic structure for any of the minor translocases remains unknown. Prior results from circular dichroism (CD), structural modeling, and AlphaFold predictions suggested these proteins have three-dimensional structures as alpha helical bundles. We have expressed and purified the T3SS translocases IpaC, SipC, and BipC from Shigella, Salmonella, and Burkholderia, respectively. Our results of CD spectroscopy, thermal denaturation, and 2D NMR show that IpaC, SipC, and BipC are alpha helical proteins, but they lack tertiary structures. The highest level of protein structures for these translocases are secondary structures. IpaC and SipC are predominantly alpha helical, whereas BipC also contains a significant amount of random coil conformation. Our results suggest that the translocon is assembled from proteins that lack tertiary structures.